Meta‐Modeling‐Based Groundwater Remediation Optimization under Flexibility in Environmental Standard. (1st May 2017) - He, Li; Xu, Zongda; Fan, Xing; Li, Jing; Lu, Hongwei
ABSTRACT: : This study develops a meta‐modeling based mathematical programming approach with flexibility in environmental standards. It integrates numerical simulation, meta‐modeling analysis, and fuzzy programming within a general framework. A set of models between remediation strategies and remediation performance can well guarantee the mitigation in computational efforts in the simulation and optimization process. In order to prevent the occurrence of over‐optimistic and pessimistic optimization strategies, a high satisfaction level resulting from the implementation of a flexible standard can indicate the degree to which the environmental standard is satisfied. The proposed approach is applied to a naphthalene‐contaminated site in China. Results show that a longer remediation period corresponds to a lower total pumping rate and a stringent risk standard implies a high total pumping rate. The wells located near or in the down‐gradient direction to the contaminant sources have the most significant efficiency among all of remediation schemes.